The Diversity and Function of Soil Bacteria and Fungi Under Altered Nitrogen and Rainfall Patterns in a Temperate Steppe - Yu, Yang; Liu, Lu; Zhao, Jianing; Wang, Shuchen; Zhou, Yijun; Xiao, Chunwang (Frontiers in Microbiology, 2022)
The response of soil microorganisms to altered nitrogen and rainfall patterns play an important role in understanding ecosystem carbon and nitrogen cycling under global change. Previous studies have separately focused on the effects of N addition and rainfall on soil microbial diversity and community composition. However, the combined and interactive impact of nitrogen addition and rainfall on soil microbial diversity and function mediated by plant and soil processes have been poorly researched for grassland ecosystems. Here, we conducted a field experiment with simulated N addition (N addition: 10 g N m-2 yr-1), altered rainfall pattern (control, rainfall reduction (compared control -50%); rainfall addition (compared control +50%)) and their interactive effects on soil microbial diversity and function in a temperate steppe of Inner Mongolia. Our results showed that N addition and rainfall addition significantly increased soil bacterial diversity, and the bacterial diversity was positively correlated with soil microbial biomass nitrogen, inorganic nitrogen, and Stipa krylovii root exudate C:N ratio, Allium polyrhizum root exudate C and N, and A. polyrhizum root exudate C:N ratio. N addition and rainfall reduction significantly reduced fungal diversity which was affected by soil microbial biomass carbon and the C:N ratio of A. polyrhizum root exudates. Bacteria were mainly eutrophic r-strategists and the responses of bacterial function guilds to the interaction of N addition and rainfall pattern were not significant. However, the arbuscular mycorrhizal fungi (AMF), in the functional classification of fungi, were significantly reduced under the condition of N addition and rainfall reduction, and the absolute abundance of the phylum Glomeromycota increased under rainfall addition, suggesting that AMFs are sensitive to altered nitrogen and rainfall patterns over short timescales (one year). Collectively, our results have important implications for understanding the plant-soil-microbe system of grasslands under climate change.